Unexpected microbial metabolic responses to elevated temperatures and nitrogen addition in subarctic soils under different land-use ... - Schroeder, Julia; Peplau, Tino; Gregorich, Edward; Tebbe, Christoph C.; Poeplau, Christopher (Zenodo, 2022)
This repository contains all necessary raw data as well as the R code used to conduct statistical analysis and create figures of the publication Unexpected microbial metabolic responses to elevated temperatures and nitrogen addition in subarctic soils under different land-use Julia Schroeder1, Tino Peplau1, Edward Gregorich2, Christoph C. Tebbe3, Christopher Poeplau1 1 Thünen Institute of Climate-Smart Agriculture, Bundesallee 68, 38116 Braunschweig, Germany2 Research and Development Centre, Central Experimental Farm, Agriculture and Agri-Food Canada, Ottawa, Canada3 Thünen Institute of Biodiversity, Bundesallee 65, 38116 Braunschweig, Germany DOI: https://doi.org/10.1007/s10533-022-00943-7 This study investigated how subarctic soils under different land use will respond to warming and increasing N availability to allow for better predictions of C cycling under global change. The short-term temperature sensitivity as well as N-input effects on microbial CUE, respiration, growth and turnover were assessed in ... : This study was part of the "Breaking the Ice" project funded by the German Research Foundation (DFG) [grant number 401106790]. Funding for E.G. was provided by the Science & Technology Branch of Agriculture & Agri-Food Canada [Project J-001756 'Biological Soil Carbon Stabilisation']. ...